Unlocking the potentials of nitrate transporters at improving plant nitrogen use efficiency - Aluko, Oluwaseun Olayemi; Kant, Surya; Adedire, Oluwafemi Michael; Li, Chuanzong; Yuan, Guang; Liu, Haobao; Wang, Qian (Frontiers in Plant Science, 2023)
Nitrate (NO3-) transporters have been identified as the primary targets involved in plant nitrogen (N) uptake, transport, assimilation, and remobilization, all of which are key determinants of nitrogen use efficiency (NUE). However, less attention has been directed toward the influence of plant nutrients and environmental cues on the expression and activities of NO3- transporters. To better understand how these transporters function in improving plant NUE, this review critically examined the roles of NO3- transporters in N uptake, transport, and distribution processes. It also described their influence on crop productivity and NUE, especially when co-expressed with other transcription factors, and discussed these transporters' functional roles in helping plants cope with adverse environmental conditions. We equally established the possible impacts of NO3- transporters on the uptake and utilization efficiency of other plant nutrients while suggesting possible strategic approaches to improving NUE in plants. Understanding the specificity of these determinants is crucial to achieving better N utilization efficiency in crops within a given environment.